Dynamic characterisation of wind turbine towers account for a monopile foundation and different soil conditions. Issue 7 (3rd July 2017) - Galvín, Pedro; Romero, Antonio; Solís, Mario; Domínguez, José
Abstract : The response of wind turbines is induced by dynamic loads such as wind, transient and cyclic loads, and also extreme loads such as earthquakes. Thus, the structural design requires an accurate evaluation of the modal parameters of the system because it is strongly required that no resonances are excited. Moreover, it has been concluded from previous research works that soil–structure interaction (SSI) should be accounted for the analysis. In the present paper, the structural dynamic response of wind turbine towers is investigated considering different soil conditions using a numerical model. This research is focused on SSI effects. Firstly, changes in the modal parameters of three different wind turbines considering the effect of three soils are evaluated. The results show that the evaluation of the natural frequency and the resulting classification of the wind turbine design type can be affected by SSI. The obtained results could be used to evaluate the decrement of the natural frequency of the wind turbine account for the soil and the foundation in relation to the frequency computed without soil interaction. Next, the seismic response of the wind tower is analysed considering two seismic events: a horizontally polarised shear incident wave and El Centro earthquake.